2020
DOI: 10.35928/cr.vol16.2018.77
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre el desempeño financiero y el desempeño de sostenibilidad: evidencias de reportes del GRI en Perú

Abstract: El desempeño e información de sostenibilidad son parte importante en la gestión de las empresas a nivel mundial, por lo que su investigación tiene un significativo desarrollo. Las empresas latinoamericanas y peruanas también han participado en iniciativas de información bajo el modelo del Global Reporting Initiative (GRI) debido a la influencia de las asociaciones empresariales y grupos de interés, a pesar de la falta de una regulación gubernamental. El objetivo del presente estudio es contribuir a la investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…The first group of papers can be classified as those that study the relationship between company size and sustainability information. In this regard, studies on Brazilian companies find that their size and availability of resources influence the level of environmental and sustainability reporting (Giacomini et al, 2018;Vogt et al, 2017), and the same relationship is also found in Peruvian and Argentine companies (Rabasedas, 2018;Hernández-Pajares, 2018a;Pocomucha & Venegas, 2021). On the other hand, it has been found that larger companies are those that present a higher level of verification in their sustainability reporting (Sierra-García et al, 2014;Zorio-Grima et al, 2015;Pastor et al, 2019).…”
Section: Quantitative Relational and Explanatory Studies Of Variablesmentioning
confidence: 82%
“…The first group of papers can be classified as those that study the relationship between company size and sustainability information. In this regard, studies on Brazilian companies find that their size and availability of resources influence the level of environmental and sustainability reporting (Giacomini et al, 2018;Vogt et al, 2017), and the same relationship is also found in Peruvian and Argentine companies (Rabasedas, 2018;Hernández-Pajares, 2018a;Pocomucha & Venegas, 2021). On the other hand, it has been found that larger companies are those that present a higher level of verification in their sustainability reporting (Sierra-García et al, 2014;Zorio-Grima et al, 2015;Pastor et al, 2019).…”
Section: Quantitative Relational and Explanatory Studies Of Variablesmentioning
confidence: 82%
“…Cochran (1981) precisa que la deficiencia se da por la imperfecta gestión, inadecuada direccionalidad de la empresa, presión sobre fondos, volatilidad del mercado, falta de enfoque y carente gestión del tiempo. Asimismo, con el pasar de los años las perspectivas de desempeño en las entidades han cambiado, en la actualidad gran parte de las regiones y sectores económicos mundiales definen que una medida adecuada es alcanzar la confianza de los grupos de interés, adjudicar financiamiento y la optimización del riesgo (García-Tamayo et al, 2022;Hernández-Pajares, 2018).…”
Section: Introductionunclassified